Animal models of membranous nephropathy: more choices and higher similarity - Pan, Ying; Chen, Si; Wu, Lin; Xing, Changying; Mao, Huijuan; Liang, Hongwei; Yuan, Yanggang (Frontiers in Immunology, 2024)
Membranous nephropathy (MN) is an antibody-mediated autoimmune glomerular disease in which PLA2R1 is the main autoantibody. It has become the most common cause of adult nephrotic syndrome, and about one-third of patients can progress to end-stage kidney disease, but its pathogenesis is still unclear. Animal models can be used as suitable tools to study the pathogenesis and treatment of MN. The previous Heymann nephritis rat model and C-BSA animal model are widely used to study the pathogenesis of MN. However, the lack of target antigen expression in podocytes of model animals (especially rodents) restricts the application. In recent years, researchers constructed animal models of antigen-specific MN, such as THSD7A, PLA2R1, which more truly simulate the pathogenesis and pathological features of MN and provide more choices for the follow-up researchers. When selecting these MN models, we need to consider many aspects, including cost, difficulty of model preparation, labor force, and whether the final model can answer the research questions. This review is to comprehensively evaluate the mechanism, advantages and disadvantages and feasibility of existing animal models, and provide new reference for the pathogenesis and treatment of MN.